2023
DOI: 10.1182/bloodadvances.2022009379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute myeloid leukemia molecular measurable residual disease testing in an interlaboratory study

Abstract: The European LeukaemiaNet (ELN) measurable residual disease (MRD) working group have published consensus guidelines to standardise molecular genetic MRD testing of the t(8;21)(q22;q22.1) RUNX1::RUNX1T1, inv(16)(p13.1q22) CBFB::MYH11, t(15;17)(q24.1;q21.2) PML::RARA and NPM1 type A markers. A study featuring 29 international laboratories was performed to assess interlaboratory variation of testing, and the subsequent interpretation of results, both crucial to patient safety. The majority of participants in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…However, the use of different transcripts makes comparisons between different assays difficult. Furthermore, the same qPCR tests run in different laboratories, e.g., for testing mutated NPM1 , may lead to discrepant results [ 23 ]. Although the sensitivity of MRD detection using PCR was high, Scott et al were able to demonstrate an issue with NPM1 analysis in an interlaboratory study.…”
Section: Current Methods Of Mrd Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of different transcripts makes comparisons between different assays difficult. Furthermore, the same qPCR tests run in different laboratories, e.g., for testing mutated NPM1 , may lead to discrepant results [ 23 ]. Although the sensitivity of MRD detection using PCR was high, Scott et al were able to demonstrate an issue with NPM1 analysis in an interlaboratory study.…”
Section: Current Methods Of Mrd Detectionmentioning
confidence: 99%
“…During the process of reverse transcription before analysis, errors in NPM1 exon 12 can be introduced artificially. As NPM1 is regarded as a leukemia-specific mutation, falsely positive MRD results could lead to unnecessary treatment [ 23 ]. Therefore, current efforts undertaken by groups, such as the ELN–DAVID MRD Working Group, focus on standardization and quality control of qPCR-based MRD assays to generate comparable MRD results [ 24 ].…”
Section: Current Methods Of Mrd Detectionmentioning
confidence: 99%
“…Further to this, external quality assessment (EQA) programs have been established to assess the quality of testing [ 4 ], For molecular MRD testing, EQA data has shown that interlaboratory variation for molecular AML MRD testing was substantially greater than that seen for BCR :: ABL1 testing in chronic myeloid leukemia (CML), despite both tests being reverse transcription quantitative PCR-based (Fig. 1 ) [ 5 , 6 ]. However, BCR :: ABL1 MRD testing has been subject to many years of standardization, including the development of the BCR :: ABL1 international scale (IS) [ 7 ].…”
Section: To the Editormentioning
confidence: 99%
“…
Fig. 1 Comparison of interlaboratory variation for standardized BCR :: ABL1 IS RT-dPCR (gray triangle markers) and RT-qPCR (black triangle markers) [ 5 ] testing with unstandardized RUNX1 :: RUNX1T1 (blue circle markers), CBFB :: MYH11 (red circle markers), PML :: RARA (green circle markers) and NPM1 (orange circle markers) RT-qPCR testing [ 6 ].
…”
Section: To the Editormentioning
confidence: 99%